Variations in Division of Sciatic Nerve and its Clinical Relevance: A Cadaveric Study - Shalom Elsy Philip; Dakshayani K.R (Academia Anatomica International, 2019)
Introduction:The sciatic nerve emerges through the greater sciatic foramen, leaves pelvis and enters into gluteal region by passing below piriformis as a single nerve encompassed by a single epineural sheath. It descends along back of thigh and divides into tibial nerve and common peroneal nerve, usually at superior angle of popliteal fossa. Understanding of variations in the levels of division of sciatic nerve is important for the management of non- discogenic sciatica, posterior hip operations, failed sciatic nerve block. Objective: To study the variations in division of sciatic nerve and to define the level of its exit.Subjects and Methods:Seventeen cadavers (34 limbs) fixed in formalin were dissected and studied during routine dissection in department of Anatomy, Mysore Medical College and level of division of sciatic nerve were noted.Results:Out of 34 limbs, 5 cases (14.7%) were dividing at gluteal region, 2 cases (5.8%) at mid-thigh and 27 cases (79.4%) exited pelvis as a whole nerve and divided at superior angle of popliteal fossa. Type G was most common variation.Conclusion:The exit and level of division of sciatic nerve is important for surgeons as there is surgical maneuvering in this region during posterior hip operations and to avoid iatrogenic nerve injury during deep intramuscular injections in gluteal region.